2023
DOI: 10.1002/smll.202207381
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Exosome SORL1 Detection Platform Based on 3D Porous Microfluidic Chip and its Application in Early Diagnosis of Colorectal Cancer

Abstract: Exosomes are promising new biomarkers for colorectal cancer (CRC) diagnosis, due to their rich biological fingerprints and high level of stability. However, the accurate detection of exosomes with specific surface receptors is limited to clinical application. Herein, an exosome enrichment platform on a 3D porous sponge microfluidic chip is constructed and the exosome capture efficiency of this chip is ≈90%. Also, deep mass spectrometry analysis followed by multi‐level expression screenings revealed a CRC‐speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 65 publications
0
16
1
Order By: Relevance
“…According to the findings in Figure 3C, hsa_circ_0124554 may be more useful than CA19-9 in the diagnosis of patients with suspected CRC. Studies have reported that the AUC of CEA in the diagnosis of CRC ranged from 0.709 to 0.739, [25][26][27] but our data showed that the AUC of CEA was 0.831, which may be related to the insufficient sample size in our study. In addition to evaluating the performance of each single marker in detection, we also combined 2 or 3 tumor markers to find the optimal diagnostic combination.…”
Section: Discussioncontrasting
confidence: 65%
“…According to the findings in Figure 3C, hsa_circ_0124554 may be more useful than CA19-9 in the diagnosis of patients with suspected CRC. Studies have reported that the AUC of CEA in the diagnosis of CRC ranged from 0.709 to 0.739, [25][26][27] but our data showed that the AUC of CEA was 0.831, which may be related to the insufficient sample size in our study. In addition to evaluating the performance of each single marker in detection, we also combined 2 or 3 tumor markers to find the optimal diagnostic combination.…”
Section: Discussioncontrasting
confidence: 65%
“…The results showed that the approach had a high accuracy with an area under curve (AUC) of 0.81 in diagnosing pancreatic cancer, indicating its potential for use in clinical settings as a non-invasive diagnostic tool. As another example, Li et al [ 79 ] developed a new method for detecting colorectal cancer using exosomes as a specific protein biomarker. They created a microfluidic chip with a 3D porous sponge structure and functionalized it with CD9 antibodies to capture exosomes flowing through the microfluidic channel.…”
Section: Lab-on-a-chip In Cancer Detectionmentioning
confidence: 99%
“…Extracellular vesicles derived from tumor cells, which can be stably detected in various body fluids and reflect the tumor burden status in real time, are considered a promising tool for liquid biopsy. Li et al functionalized a 3D porous PDMS sponge structure with CD9 antibody to capture extracellular vesicles imported into a microfluidic chip [ 234 ]. This work is based on a 3D porous microfluidic chip platform and is used as a new non-invasive diagnostic tool for the early detection of colorectal cancer.…”
Section: Microfluidic Devices Based On Porous Media For Biomedical An...mentioning
confidence: 99%